Long-term impact of SARS-CoV-2 infection on cardiorespiratory fitness: a meta-analysis - Chuatrakoon, Busaba; Konghakote, Supatcha; Sa-nguanmoo, Piangkwan; Nantakool, Sothida (Frontiers in Public Health, 2023)
Despite surviving Coronavirus disease 2019 (COVID-19),its long-term impact is of concern. Low cardiorespiratory fitness is a strong predictor of all-cause mortality,and likely affected by multisystem impairments following COVID-19 infection. Accumulating evidence has identified the impact of COVID-19 on cardiorespiratory fitness level. However,the findings have been controversial. Conclusive evidence is still needed. This review aimed to systematically summarize and synthesize whether the SARS-CoV-2 infection diminishes cardiorespiratory fitness in COVID-19 survivors. The study design was a systematic review and meta-analysis. A search was carried out using PubMed,CINAHL,Scopus,Embase and the Cochrane Library,together with reference lists (searching from their inception to January 2023). Observational studies investigating the impact of COVID-19 on outcomes relevant to cardiorespiratory fitness [i.e.,peak oxygen uptake] were included. Weighted mean difference(WMD) and 95%confidence interval(CI) were used to identify a pooled effect estimate. Use of a random effects model was considered as the main method. Grading of Recommendation Assessment, Development and Evaluation approach was employed to determine the certainty of evidence. This meta-analysis was registered with PROSPERO(registration number:CRD42023393108). Seven eligible studies (4 cross-sectional,2 cohort,and 1 case-control studies) involving 4,773 participants were included in this meta-analysis. A pooled effect estimates showed that patients in the surviving COVID-19 group had a significant reduction in peak oxygen uptake when compared to their counterparts in the non-COVID-19 group (WMD-6.70,95%CI-9.34 to-4.06,low certainty). A subgroup analysis by age found that COVID-19 survivors in the young- to middle-aged and middle-to older-aged subgroups had significant reductions in peak oxygen uptake when compared to their counterparts in the non-COVID-19 group(WMD-5.31,95%CI-7.69 to-2.94,low certainty;WMD-15.63, 95%CI-28.50 to-2.75,very low certainty,respectively). Subgroup analyses by symptom found that patients with moderate to severe symptoms in the surviving COVID-19 group had significantly lower peak oxygen uptake than their counterparts in the non-COVID-19 group (WMD-15.63,95%CI-28.50 to-2.75,very low certainty). The current meta-analysis concluded that patients in the COVID-19 survivors had poorer cardiorespiratory fitness than their counterparts in the non-COVID-19 group, but there is considerable uncertainty of evidence. Poorer cardiorespiratory fitness is likely to be more pronounced in COVID-19 survivors who are getting older and had severe symptoms, but it is uncertain whether such finding has a valuable in clinical context.